Developing an Android-based Screen Lock Application for Arabic Vocabulary Enrichment of the Tenth Graders at the Madrasah Aliyah - Tohe, A; Aliyudin Al-Ayubi, M; Maksum, A (KnE Social Sciences, 2019)
This research aims at developing an Android-based screen lock application for Arabic vocabulary enrichment of the Tenth Grade Students at the Madrasah Aliyah. The research design used is the research and development model proposed by Borg & Gall, with some modification, according to the research needs. The Data are gathered through scoring sheets and then analyzed using descriptive and percentage techniques. The end result of the research is an Android-based screen lock application that consists of seventy sets of Arabic vocabulary, containing three hundred Arabic words. These vocabulary items are presented randomly on the handphone’s screen as a set of questions whose correct answers will allow students to have access to their phones. The results of the research demonstrate that according to the expert and field test the application is valid, with each of the content and appearance experts scored 82%, and both teacher and students at the school scored 95% and 81%, respectively. Keywords: Android, screen lock, application, Arabic vocabulary, tenth grade, Madrasah Aliyah